(untitled) (Nexo Revista Científica, 2023)
The Maya Train is one of the most important projects of the current Mexican government. Although, at first glance, it seems attractive for tourism and will facilitate transportation through the Yucatan peninsula, it will also have repercussions that will be detrimental not only environmentally, but also socially and economically in the future. The main objectives of this article are to identify, describe and explain the environmental, social and economic impacts that the construction of the Maya Train will have on the indigenous peoples of Chiapas, Tabasco, Campeche, Yucatan, and Quintana Roo. This is theoretical research with a qualitative approach, since it is expected to inform and emphasize the consequences and benefits that the construction of the Mayan Train will have on the lives not only of human beings, but also of living beings in general. For this purpose, academic search engines such as Google Scholar, Redalyc, Dialnet, Scielo and ResearchGate were used.